Concerning the latent content of psychoanalytic concepts: Some con-jectures - Zepf, Siegfried; Seel, Dietmar (Advances in Social Sciences Research Journal, 2021)
Many psychoanalysts understand their concepts as metaphors, yet they do not question what is expressed metaphorically in these concepts. Based on the view that the real cognitive subject is society and the cognizing individual is their individual existence, the authors show by means of some of these concepts that such metaphors are mystified expressions of the socially unconscious as described by Marx & Engels.